Gender Bias in the Reelection of Politicians (When a Crisis Strikes) - Zohal Hessami; Temurbek Khasanboev (Institute of Labor Economics (IZA), 2024)
This paper sheds light on a neglected reason for women's underrepresentation in politics: crisis-induced gender gaps in incumbents' reelection with lasting negative effects on female representation. We use hand-collected data on 173,339 candidates in open-list local council elections (1997-2021) in the German state of Hesse. We exploit the March 2021 election one year into the Covid-19 pandemic and exclusive local Covid-19 mortality data in a continuous DiD framework. In a setting where (individual) councilors had no role in fighting the pandemic, we provide robust evidence for a gender blame attribution gap: at an average of one death/1,000 inhabitants, an additional death (≈ one SD treatment) leads to a 4.3 and 7.8 ppt lower reelection probability for male and female incumbents, respectively. Further results exclude various alternative mechanisms. Simulations predict persistent negative effects on future female councilor shares of 3-4 ppts.
Keywords: D72; H12; H70; I18; J16; 330; gender; retrospective voting; incumbency; crisis; local elections; political selection